A review on Zeolite-Reinforced Polymeric Membranes: Salient Features and Applications. (11th December 2016) - Tul Muntha, Sedra; Kausar, Ayesha; Siddiq, Muhammad
ABSTRACT: Various types of synthetic polymeric membranes have been fabricated for separation purposes in industry/laboratory. Zeolite is ceramic-based material and well known for its antiwear resistance and high mechanical strength. Mixed matrix membranes are the latest membrane technology constituting inorganic nanoparticle phase and organic polymer phase. The review represents various types and applications of zeolite-reinforced polymeric membranes. Consequently, fabrication procedure and working principle of zeolite-reinforced mixed matrix (polyimide, polysulfone, polycarbonate) membranes have been discussed. The significant relevance of polymer/zeolite membranes is in water purification, medical, catalytic, and gas separation industries. Improvement in polymeric membrane properties has been observed through incorporation of zeolite filler. GRAPHICAL ABSTRACT: